Cell senescence contributes to tissue regeneration in zebrafish. Issue 1 (31st October 2019) - Da Silva‐Álvarez, Sabela; Guerra‐Varela, Jorge; Sobrido‐Cameán, Daniel; Quelle, Ana; Barreiro‐Iglesias, Antón; Sánchez, Laura; Collado, Manuel
Abstract: Cellular senescence is a stress response that limits the proliferation of damaged cells by establishing a permanent cell cycle arrest. Different stimuli can trigger senescence but excessive production or impaired clearance of these cells can lead to their accumulation during aging with deleterious effects. Despite this potential negative side of cell senescence, its physiological role as a pro‐regenerative and morphogenetic force has emerged recently after the identification of programmed cell senescence during embryogenesis and during wound healing and limb regeneration. Here, we explored the conservation of tissue injury‐induced senescence in a model of complex regeneration, the zebrafish. Fin amputation in adult fish led to the appearance of senescent cells at the site of damage, and their removal impaired tissue regeneration. Despite many conceptual similarities, this tissue repair response is different from developmental senescence. Our results lend support to the notion that cell senescence is a positive response promoting tissue repair and homeostasis. Abstract : Tissue injury‐induced senescence is conserved in zebrafish. Fin amputation in adult fish lead to the appearance of senescent cells at the site of damage, and their removal impairs tissue regeneration. Tissue injury‐induced senescence is different from developmental senescence.